Legal Improvement of Liability Measures for Violation of Environmental Safety Requirements in the Energy Sector - o’g’li, Nishonov Abdulloh Ubaydulloh (American Journal of Biodiversity, 2025)
This article is dedicated to improving liability measures for violations of environmental safety requirements in the energy sector of Uzbekistan. It analyzes the perspectives of international scholars Philippe Sands, Jacqueline Peel, Adriana Fabra, Ruth MacKenzie, Michael Faure, and Stephen Stec, examining the legal, financial, technological, and strategic aspects of environmental damage and liability, highlighting the complementary nature of their approaches. Based on this analysis, the article proposes innovative solutions that have not yet been implemented in Uzbekistan’s legislation: dynamic liability algorithms, an environmental simulation database for energy projects, eco-liability tokens, an AI-based transboundary environmental risk prevention system, and an eco-innovative certification platform. The implementation of these approaches can significantly enhance environmental damage prevention, compensation mechanisms, and ensure the sustainable and safe execution of energy projects.